ANALISIS PENERAPAN TEKNOLOGI PENANGGULANGAN HAMA PENYAKIT PADA USAHATANI CABAI MERAH DATARAN TINGGI DI PROVINSI BENGKULU - Astuti, Herlena Bidi; Fauzi, Emlan; Yahumri, Yahumri; Hartono, Rudi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2016)
Red chili is one of national strategic commodity, can affect the rate of inflation and is needed by all levels of society. Pest attack often makes low production and the high demand makes price of chili is very high. The aim of this study was to determine the application of pest management technology in farming chili crop in the highlands Province of Bengkulu. The research was conducted in Rejang Lebong and Lebong purposively determined by number of respondents as many as 62 people were taken by random sampling. The results showed an average score of application of crop pest management technology red chili is 2,38 meaning that the overall implementation of technology is not good. 37,5% reduction technology implementation pepper plant pests and diseases in the category is not good that the use of biological pesticides, use of trap insect, and growing border. 37,5% are categorized either using labeled seeds, sanitary land and land preparation is perfect. 25% excellent category that is sprayed with chemicals and use black plastic mulch silver.